2022
DOI: 10.3390/biomedicines10020249
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability in Patients with Non-Alcoholic Fatty Liver Disease (NAFLD): Causes and Consequences

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease, and it is anticipated that it could become even more prevalent in parallel with an increase in the incidence of metabolic diseases closely related to NAFLD, such as obesity, type II diabetes, dyslipidemia, and arterial hypertension. In addition to liver impairment, NAFLD is associated with cardiovascular diseases. Fibrosis, atherosclerosis, and venous thrombosis are basically the pathogenic mechanisms behind these clinical mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 62 publications
0
21
0
1
Order By: Relevance
“…Among these mechanisms, impaired iron metabolism and increased iron stores that are frequently observed in patients with NAFLD might activate oxidative stress and thereby unfavorably affect cardiovascular functions ( 42 ). Also, a prothrombotic state that is frequently detected in patients with fatty liver ( 43 ) might contribute to the development and progression of hypertension-related cardiac damage ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these mechanisms, impaired iron metabolism and increased iron stores that are frequently observed in patients with NAFLD might activate oxidative stress and thereby unfavorably affect cardiovascular functions ( 42 ). Also, a prothrombotic state that is frequently detected in patients with fatty liver ( 43 ) might contribute to the development and progression of hypertension-related cardiac damage ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Доказано, что MPV положительно коррелирует с баллом по шкале SYNTAX и относится к числу предикторов неблагоприятного прогноза при ИМ [26,27]. Другими причинами повышенного тромбообразования при МАЖБП могут служить системная гипекоагуляция и нарушение фибринолиза [28,29].…”
Section: материалы и методыunclassified
“… 4 Based on cross-sectional case-control studies, we and others reported that NAFLD may tip the coagulation balance towards thrombosis more than other liver conditions, 5 but evidence is still controversial. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“… 3 Furthermore, systematic assessment of the regulation of the coagulation balance in well-characterised, unselected cohorts of individuals with metabolic risk factors, and of the causal relationship with liver damage, is still lacking. 7 …”
Section: Introductionmentioning
confidence: 99%